2008
DOI: 10.1016/j.neuropsychologia.2008.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Viewing it differently: Social scene perception in Williams syndrome and Autism

Abstract: The genetic disorder Williams syndrome (WS) is associated with a propulsion towards social stimuli and interactions with people. In contrast, the neuro-developmental disorder autism is characterised by social withdrawal and lack of interest in socially relevant information. Using eye-tracking techniques we investigate how individuals with these two neuro-developmental disorders associated with distinct social characteristics view scenes containing people. The way individuals with these disorders view social st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
350
7
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 314 publications
(383 citation statements)
references
References 27 publications
23
350
7
3
Order By: Relevance
“…This result is strikingly different to the results obtained by Riby and Hancock (2008). They found that fixations on regions containing the eyes in photographic scenes were markedly reduced in their sample of individuals with ASD.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…This result is strikingly different to the results obtained by Riby and Hancock (2008). They found that fixations on regions containing the eyes in photographic scenes were markedly reduced in their sample of individuals with ASD.…”
Section: Discussioncontrasting
confidence: 90%
“…This explanation Eye-tracking in Autism 26 seems likely as Leekam et al (1998) demonstrated that mental age is a strong predictor of social ability in individuals with ASD. The difference in nature of the results between the current studies and those obtained by Riby and Hancock (2008) highlights the need to refrain from generalising results beyond the population involved in individual studies. The results of the current study are more similar to those recently obtained by Fletcher-Watson, Leekam, Benson, Frank and Findlay (2009) who ran an eye-tracking study with a similar cohort of participants to those in the current study.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Ashwin, Ricciardelli, & Baron-Cohen, 2009). Indeed previous work using eye-tracking techniques has indicated that ASD individuals spend less time than do typical individuals viewing people and faces in social situations (Mercadante, Macedo, Baptista, Paula, & Schwartzman, 2006;Riby & Hancock, 2009;Riby & Hancock, 2008), and future work would be valuable in utilising these eye tracking techniques to examine the role of directed attention on salient social and person aspects of an event and its effect on subsequent memory recall in an eyewitness paradigm. That the ASD group were significantly more accurate for Surrounding details when interviewed with SIs is not unexpected given that these types of details can be relatively separated from person and action details and might rely on more of a rote memory strategy.…”
Section: Insert Tablementioning
confidence: 99%
“…This atypical social behaviour has attracted significant research interest, particularly in recent years (e.g. Haas et al, 2009;Plesa-Skwerer et al, 2008;Riby & Hancock, 2008, 2009a, 2009b. In keeping with the methodology used in the present research, an interesting possibility is that the unusual social behaviour observed in WS may be related to a bias in the interpretation of social situations.…”
Section: Interpretation Bias and Social Behaviour In Williams Syndromementioning
confidence: 72%